Proceedings of the 6th Workshop on Computational Approaches to Subjectivity, Sentiment and Social Media Analysis 2015
DOI: 10.18653/v1/w15-2918
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Sentiment: Social Psychological Analysis of Political Facebook Comments in Hungary

Abstract: This paper presents the methodology and results of a project for the large-scale analysis of public messages in political discourse on Facebook, the dominant social media site in Hungary. We propose several novel social psychologymotivated dimensions for natural language processing-based text analysis that go beyond the standard sentiment-based analysis approaches. Communion describes the moral and emotional aspects of an individual's relations to others, while agency describes individuals in terms of the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Public comments written in response to political posts on Facebook were investigated using novel socio-psychological measures. Data suggest that comments associated with sentiments of communitarian thinking were more frequent during the campaign period for the general election of 2014 (Miháltz et al 2015).…”
Section: Figure 3: Proportion Of Respondents Who Use Facebook For News (Reuters Institute Digitalmentioning
confidence: 96%
“…Public comments written in response to political posts on Facebook were investigated using novel socio-psychological measures. Data suggest that comments associated with sentiments of communitarian thinking were more frequent during the campaign period for the general election of 2014 (Miháltz et al 2015).…”
Section: Figure 3: Proportion Of Respondents Who Use Facebook For News (Reuters Institute Digitalmentioning
confidence: 96%
“…The sentiments of Facebook users with respect to 187 politicians after the 2013 German federal elections were analysed in order to assess public opinions (Caton et al, 2015). Mihaltz et al (2015) analysed 1.9 million political Facebook comments to determine past, present and future optimism. In a study on MySpace, it was found that female users tend to receive and give more positive comments than male users although there is no significant difference for negative comments (Thelwall et al, 2010).…”
Section: Related Workmentioning
confidence: 99%